Influence of mulching and irrigation level on water-use efficiency, plant growth and quality of strawberry (Fragaria ananassa) - SURESH KUMAR, P; CHOUDHARY, V K; BHAGAWATI, R (The Indian Journal of Agricultural Sciences, 2012)
Strawberry (Fragaria × ananassa Duch) cv. Chandler was grown in the field to investigate the effectiveness of different mulches and irrigation level on plant growth, fruit growth, yield and other quality parameters. I1 favoured plant growth, enhanced flowering (67.5 days), resulted in production of significantly larger fruit and higher yield (175.15 g/ plant), higher TSS, and ascorbic acid content with lesser incidence of albinism (17.9%) and botrytis rot than other irrigation levels. Plants mulched with BPM have significantly better growth, flowered and fruited early, produced larger fruit and higher yield, with slightly higher incidence of albinism (19.8%), but with lower incidence of botrytis rot (14.9 %) than those mulched with other materials. Irrigation level × mulching interaction has significantly influenced growth parameters like, crown height, plant spread and leaf area with I1 × M1 interaction. Strawberry produced larger fruit (13.1 g) and higher yield (185.8 g/plant), higher TSS, and higher ascorbic acid content with a slightly higher incidence of albinism, but comparatively lower incidence of botrytis rot under irrigation regime of I1 mulched with black polyethylene.